PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 35 PEKANBARU - Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The results of study that fall into the low category is the background in research this study, ie with average learning outcome of 65.00. This research is a classroom action research that aims to improve student learning outcomes through the application of STAD type cooperative learning model. The data used in this research is teacher and student activity data and student learning result of IPS. The result of research indicates that the students' learning achievement has increased, this is proved by: Activity of teacher at cycle 1 meeting 1 equal to 58,30%, at cycle 1 meeting 2 equal to 62,50%, increase in cycle II meeting 1 up to 79,2% , increased in the second cycle of meetings 2 to 91.67%. The activity of the students in the 1st cycle of meeting 1 was 54,2%, in the 1st cycle of meeting 2 was 58,30%, increase in cycle II of meeting 1 to 75,00%, increased in cycle II meeting 2 until 87,50%. Student learning outcomes in prasiklus amounted to 55.40, increased in the cycle I to 68.40, and in the second cycle increased to 76.80.